Targeting radiation‐induced upstream stimulatory factor‐1 by histone deacetylase inhibitors to reverse radioresistance in prostate cancer. Issue 12 (17th September 2021) - Gupta, Seema; Ahmed, Mansoor M.
Abstract: Background: Ionizing radiation (IR) is a standard modality for the management of solid tumors. Apart from its killing effects, IR can induce pro‐survival factors leading to radioresistance of cancer. Mechanistic understanding of radiation resistance is warranted to overcome the pro‐survival effects of IR. Aim: The aim of this study was to investigate the role of upstream stimulatory factor‐1 (USF‐1) in the induction of radioresistance in prostate cancer and its targeting by histone deacetylase (HDAC) inhibitors to reverse resistance. Methods and results: This study reports here that USF‐1 is a marker for radioresistance in PC‐3 cells. Using protein‐DNA array analysis, it was documented that DNA binding activity of USF‐1 was elevated following IR in PC‐3 cells. Novel HDAC inhibitors downregulated USF‐1 binding either alone or in combination with IR. A 5 Gy dose of IR induced the expression of target genes of USF‐1 (human telomerase reverse transcriptase [hTERT], IGF2R, CyclinB1, and Cdk1), however, HDAC inhibitors alone or in combination with IR reduced their expression as measured by real time RT PCR analysis. Furthermore, immunofluorescence analysis revealed that while USF‐1 localized primarily in the nucleus following IR, it localized in the cytoplasm when treated with HDAC inhibitors/combination. Maximum effects of modulation of USF‐1 expression (overexpression or suppression) were observed on hTERT activity as determined by dual‐luciferase reporter assay. To further confirm the role of USF‐1 in radioresistance, cell growth was analyzed using the real‐time cell electronic sensing (RT‐CES) system. This study found that USF‐1‐transfected cells proliferated faster than the vector‐transfected cells with or without treatments with HDAC inhibitors/IR/combination. Colony forming assay also confirmed that USF‐1 overexpression led to increased survival following IR. Importantly, colony‐forming assay demonstrated that HDAC inhibitors reversed the radioresistance in both PC‐3 and DU‐145 cells. Conclusion: These studies demonstrate that HDAC inhibitors reverse the radioresistance in prostate cancer through down‐modulation of USF‐1‐mediated transactivation of target genes involved in cell proliferation and cell cycle.